The history of modern Western esotericism Individuals, ideas, practices - Mahlamäki Tiina; Leskelä-Kärki Maarit (DONNER INST RESEARCH RELIGIOUS & CULTURAL HISTORY, 2022)
The study of Western esoteric traditions and practices has been a growing research field since the 1990s. This thematic issue aims at opening this field particularly in the context of Finnish cultural history, although the articles cover also other parts of the long tradition of Western esotericism in the history of Europe.